Ba1-xSrxTiO3 thin films by polymeric precursor method - Pontes, F. M.; Longo, Elson [UNESP]; Rangel, J. H.; Bernardi, M. I.; Leite, E. R.; Varela, José Arana [UNESP] (Elsevier B.V., 2000)
Stoichiometric Ba1-xSrxTiO3 (BST; x = 0.4) thin films were prepared by the polymeric precursor method. High quality polycrystalline films of BST with low roughness (approximate to 3 nm) were obtained from a Pt/Ti/SiO2/Si substrate deposited by spin-coating technique. Microstructure and morphological evaluation were done using grazing incident X-ray diffraction (GIXRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Grazing incident angle XRD characterization of these films showed that BST phase crystallizes at 600 degrees C from an inorganic amorphous matrix. No intermediate crystalline phase was identified. A linear relationship between roughness and grain size was observed. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: Ba1-xSrxTiO3; spin-coating; polymeric precursor method